2004
DOI: 10.1007/s00406-004-0492-3
|View full text |Cite
|
Sign up to set email alerts
|

Executive dysfunctions in schizophrenia

Abstract: Studies suggest that executive functions in patients with schizophrenia are markedly impaired as compared with normal controls. Most previous studies employed tests of executive functions adopted from frontal lobe neuropsychological paradigms based on lesion studies. This study employed several more recently developed theory-driven tests of executive functions addressing the construct of the supervisory attentional system. We explore the pattern of executive function impairment using factor analysis and subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 30 publications
1
20
1
2
Order By: Relevance
“…Moreover, Chan and Chen (2004b) demonstrated that significant relationships were found between specific executive function components and neurological soft signs. Specifically, motor coordination was correlated with attention inhibition component, verbal performance and visual memory; sensory integration was correlated with initiation component and verbal functioning; and disinhibition signs were associated with attention inhibition component.…”
Section: Neurological Soft Signs and Cognitive Impairmentsmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, Chan and Chen (2004b) demonstrated that significant relationships were found between specific executive function components and neurological soft signs. Specifically, motor coordination was correlated with attention inhibition component, verbal performance and visual memory; sensory integration was correlated with initiation component and verbal functioning; and disinhibition signs were associated with attention inhibition component.…”
Section: Neurological Soft Signs and Cognitive Impairmentsmentioning
confidence: 95%
“…Moreover, Chan et al (2004b) found that the disinhibition signs were associated with behavioural disinhibition task and blink rate in a group of 90 patients with chronic schizophrenia. The modest correspondence of the factor analytic data and conceptual models might be due to a number of methodological limitations.…”
Section: Categorization Of Neurological Soft Signsmentioning
confidence: 98%
“…Executive dysfunction is commonly seen following head injury (Stuss and Gow 1992) and also in a number of psychiatric (e.g. Chan et al 2004) and neurological disorders (e.g. Swanberg et al 2004) where the frontal lobes are implicated.…”
mentioning
confidence: 99%
“…Por ejemplo, Chan et al (2004), en 51 pacientes crónicos encontraron tres factores: uno de inhibición semántica, otro de inhibición de la atención/acción y otro de generación de la acción (iniciativa), así como una relación entre estos componentes y las características clínicas 23 . Estos autores también han encontrado alteraciones en componentes de la función ejecutiva en individuos con esquizofrenia crónica y en pacientes con un primer episodio, libres de medicación, como son la iniciativa, la atención sostenida, la flexibilidad al cambio, la planificación, la inhibición y la actualización 24 .…”
Section: Sujetosunclassified